Association Between MRI‐Based Radiomics Features and Regional Lymph Node Metastasis in Intrahepatic Cholangiocarcinoma and Its Clinical Outcome - Qian, Xianling; Ni, Xiaoyan; Miao, Gengyun; Wang, Fang; Zhou, Changwu; Huang, Peng; Zhang, Yunfei; Chen, Lei; Yang, Chun; Zeng, Mengsu (Journal of magnetic resonance imaging, 2025)
Background Regional lymph node metastasis (LNM) assessment is crucial for predicting intrahepatic cholangiocarcinoma (iCCA) prognosis. However, imaging assessment has limitations for identifying LNM. Purpose To investigate the association between MRI radiomics features, regional LNM status, and prognosis in iCCA. Study Type Retrospective. Subjects Two hundred ninety‐six patients (male = 197) with surgically confirmed iCCA. Field Strength/Sequence 1.5 T and 3.0 T. DWI, T2WI, and contrast‐enhanced T1WI. Assessment Clinical information, radiologic, and MRI‐based radiomics features associated with LNM status were collected to establish models. Performance of MRI, PET/CT, and the combined LNM models were compared in training (N = 207) and test (N = 89) datasets. Overall survival (OS) was compared based on LNM status. Statistical Tests The independent features were selected by 5‐fold cross‐validation. The performance of MRI, PET/CT, and the models was evaluated using the area under receiver operating characteristic curve (AUC). Univariable and multivariable Cox regression were used to identify independent variables for OS. Kaplan–Meier curves were compared with the log‐rank test between LNM positive and negative groups. P < 0.05 was considered statistically significant. Results Intrahepatic duct dilatation, enhancement pattern, and CA19‐9 were independent clinicoradiologic features. The radiomics model was constructed by the independent radiomics features extracted from T2WI and delay phase T1WI. The combined LNM model showed AUC of 0.888, 0.884, and 0.811 in training, validation, and test cohorts with a positive net benefit. PET/CT exhibited similar sensitivity to the combined LNM model (0.750 vs. 0.733, P > 0.999) while the combined LNM model showed higher specificity (0.703 vs. 0.630, P = 0.039) in the test cohort. High risk of regional LNM was significantly associated with worse OS (median: 24 months) than low risk (median: 30 months, P < 0.0001). Data Conclusions The combined LNM model has the strongest correlation with LNM status for mass‐forming iCCA patients. Evidence Level 3 Technical Efficacy Stage 2